Heterogeneously catalyzed strategies for the deconstruction of high density polyethylene: plastic waste valorisation to fuels - Burange, Anand S.; Gawande, Manoj B.; Lam, Frank L. Y.; Jayaram, Radha V.; Luque, Rafael (Green Chemistry, 2015)
The plastic industry generates enormous quantities of plastics at projected rates (both production and consumption) which can significantly threaten our environment in terms of plastic waste generation. High density polyethylene (HDPE) is one of the main fractions of municipal solid waste which has a remarkable potential to be valorised into fuels (e.g. bio-oils). Catalytic degradation is an innovative alternative process to transform plastic waste into such value added products. This mini review was aimed to discuss the most relevant and recent catalysts developed for the catalytic degradation of HDPE including metal oxides, sulphated metal oxides, zeolites, nanostructured zeolites, molecular sieves, fluid catalytic cracking (FCC) catalysts, metal carbonates and mesoporous materials for the production of chemicals and fuels (e.g. diesel and gasolines). Activities and selectivities as well as important effects of additives, particle size, catalyst to polymer ratios and also recent approaches for waste management will be discussed.

Palladium supported on fluorite structured redox CeZrO4-δ for heterogeneous suzuki coupling in water: a green protocol - Burange, Anand S.; Shukla, Rakesh; Tyagi, Avesh Kumar; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Pd on redox CeZrO4-δ catalysts was prepared, characterized and their activity was evaluated for Suzuki coupling reaction in water under reflux condition. Fresh and reduced form of 5 % Pd (R−Pd5) on CeZrO4-δ catalyst exhibited 100 % conversion in 2.5 and 1 h, respectively. R−Pd5 shows significant activity for wide range of substrate compatibility and for less reactive aryl bromides too. The mechanistic investigations proved the important role of redox CeZrO4-δ support on the catalytic activity. It was observed that the presence of oxygen vacancy along with Ce3+ enhances the activity. 1 wt % Pd photodeposited on pre-reduced CeZrO4-δ support requires a mere 20 min. for 100 % conversion of Suzuki coupling. Effect of metal dispersion and particle size on catalytic activity is also discussed. High Pd dispersion with small particle size (4±1 nm), particle size preservation after reaction, strong metal-support interaction and no leaching fully suggest the heterogeneous mechanism is operative for Suzuki coupling on 1 wt % Pd photodeposited on reduced CeZrO4-δ support. Present work hints the possibility of achieving high conversion for Suzuki reaction with very small amount of Pd through better dispersion by taking advantage of redox support and in water.

Role of palladium crystallite size on CO oxidation over CeZrO 4-δ supported Pd catalysts - Burange, Anand S.; Reddy, Kasala Prabhakr; Gopinath, Chinnakonda; Shukla, Rakesh; Tyagi, Avesh K. (Journal of Molecular Catalysis, 2018)
Photodeposited palladium on nanocrystalline CeZrO 4-δ support was evaluated for CO oxidation, as a function of particle size and pre-treatment. All the catalysts were well characterized by XRD, SEM, EDX, TEM, CO chemi-sorption and Raman spectroscopy. It was observed that change in photodeposition time alters the average crystallite size of Pd, and the same was confirmed by CO chemisorption. 7 nm average crystallite size of Pd exhibited excellent catalytic activity for CO oxidation. In order to understand the effect of support and metal-support interaction, 1 wt% Pd was deposited deliberately onto reduced and oxidized CeZrO 4-δ support. The reduced support with anionic vacancies and more Ce 3+ species exhibited an improvement in CO oxidation at onset temperature. Detailed analysis shows that Pd-deposition occurs preferentially at oxygen-vacancy sites and subsequent metal-support interaction influences the catalysis.

Shape-controlled metal oxides for selective catalytic oxidation - Burange, Anand S.; Gopinath, Chinnakonda (Advanced Heterogeneous Catalysts Volume 1: Applications at the Nano-Scale, 2020)
Some of industrial processes involve selective oxidation reactions that include the use of corrosive and nonbenign oxidants and solvents. Many metal oxide-based catalysts have been reported for selective oxidation processes, and they exhibit a range of activities compared to homogeneous protocols and current practices. To bridge the gap between homogeneous and heterogeneous catalysis in terms of activity and selectivity and move toward green oxidation processes, this chapter discusses the shape-controlled synthesis of a selected range of metal oxides and their applications in selective catalytic oxidation reactions. This chapter also discusses some of the interesting micro- and nanostructured materials used in these reactions, as well as the roles of exposed predominant facets, defects, and other features and their effects on catalysis. Oxides of Mn, Co, Ce, Cu, Fe, La, and some combinations thereof are presented. Chemical reactions such as the selective oxidations of alcohol, ethyl benzene, styrene, xylene, and 5-hydroxymethylfurfural and the preferential oxidation of CO are also discussed.

Catalytic applications of hydrotalcite and related materials in multi -component reactions: concepts, challenges and future scope - Burange, Anand S.; Gopinath, Chinnakonda S. (Sustainable Chemistry and Pharmacy, 2021)
Hydrotalcites (HTs) are the potential substitute to conventional base catalysts. HTs are useful in efficient syntheses of various heterocycles, such as chromenes, pyrans, pyrazoles, triazoles, using multi-component reactions. This review focuses on the chemistry of HTs and particularly hydrotalcites and related materials in the synthesis of heterocycles. The effects of preparation method and, physico-chemical parameters, such as calcination, molar ratio of metals, role of intercalated ions, surface area, on the catalytic activities are discussed. Along with technical aspects, this review also unlocks various untouched areas in developing sustainable catalyst for syntheses of heterocycles, drugs, etc. for the future.
Keywords: green chemistry; green synthesis; heterocycles; heterogeneous catalysis; hydrotalcite; Metal Oxide

Green synthesis of xanthene and acridine-based heterocycles of pharmaceutical importance: a review - Burange, Anand S.; Gadam, Komal G.; Tugaonkar, Prajyot S.; Thakur, Seema D.; Soni, Ravish K.; Khan, Rubej R.; Tai, Mubashira S.; Gopinath, Chinnakonda S. (Environmental Chemistry Letters, 2021)
Xanthene and acridine-based heterocyclic compounds find applications in cancer chemotherapy, biological staining and laser dyes and are known for their antibacterial and anti-tumor properties. Here we review green catalytic routes for the synthesis of 1,8-dioxo-octahydroxanthenes, 1,8-dioxo-decahydroacridines and related heterocyclic molecules with catalysts such as metal oxides, mixed metal oxides, resins, supported organocatalysts, heteropolyacids, carbon-based materials, zeolites, sulfides and ionic liquids. We compare protocols for their catalytic activities, and proposed mechanisms are discussed.
Keywords: green chemistry; heterocycles; heterogeneous catalysis; Metal oxides; nanocatalysis